POTENSI UBI JALAR (Ipomoea batatas L) UNTUK FORTIFIKASI PEMBUATAN SIRUP YANG BERCITARASA - Dina Astriana; Abdul Muis; Ilah Nurlaelah (Program Studi Pendidikan Biologi, FKIP Universitas Kuningan, 2015)
This research is motivated by a number of sweet potato production in Kuningan abundant, but the utilization of sweet potato Brass less desirable for society. In addition there is also a problem of other issues behind this research that most commercially available syrup made from fruits. Thus the number of sweet potato production in Kuningan then made a new innovation in the manufacture of syrup by using materials of sweet potato. It aims to raise local knowledge Regency Brass and provide new information for the public in using sweet potatoes. This study aims to determine whether fortification of white flour sweet potato AC brass affect the manufacture of flavored syrup so preferred by consumers and to determine how the composition of white sweet potato flour brass AC most optimal to produce the flavored syrup is preferred by consumers. This research method using a completely randomized design (CRD). Techniques of data analysis in this research is by using test oragnoleptik (flavor, aroma, viscosity and color). Analysis of the data using statistical and testing using test nonparametri friedman. Objects in this study dalah syrup and subjects in this study were the panelists, the panelists as many as 30 people. Based on the results of data processing by using the friedman test the flavor, aroma, viscosity and color of the results obtained from the four formulations of sweet potato flour resulting in a different effect on the taste, aroma, viscosity and color. In terms of flavor formulations are preferred by the panelists at the F2 formulation with the composition of sweet potato flour 50 grams, for terms of scent formulation preferred by panelists yatu contained in the formulation F4 with as much as 100 grams of flour composition, in terms of viscosity formulations are preferred by panelists yatu contained in the formulation F4 with as much as 100 grams of flour composition, and for terms of color formulations are preferred by the panelists at the F1 formulsai composition of sweet potato flour as much as 25 grams. Hypothesis testing is done by using test friedman, of all treatments showed all of which produce data that count x2 x2 table from, and it states that H0 is rejected and Hi is accepted. So for the first conclusion is that there is an effect on sweet potato flour fortification AC white brass to manufacture flavored syrup so favored by consumers, and to the conclusion that the second is the use of air conditioning composition of sweet potato flour 50 grams white brass produce optimal syrup and bercitrasa so favored by consumers. Keywords: Potential sweet potato, fortification and syrup